IMPLIKASI PELAKSANAAN PERJANJIAN JUAL BELI TELEPON SELULER ILEGAL (BLACK MARKET) - Andika Prawira Buana; Hasnan Hasbi; Muhammad Kamal; Aan Aswari (JCH (Jurnal Cendekia Hukum), 2020)
An agreement is a legal relationship between one person and another person or several persons in order to accomplish a certain thing that has been agreed upon. The Agreement becomes the Law for the parties who make and comply with the content of the agreement. In principle, the treaty embraces the principle of contractual freedom, but that freedom has certain limitations that cannot be violated for the sake of justice, usefulness and legal certainty. The purpose of this research is to describe juridically the wetness and consequences of the illegal cell phone sale and purchase agreement. This research method uses normative legal research type using secondary data and is analyzed based on juridical descriptive. The results of this study argue that the absence of a mobile phone sale agreement is illegal because it does not meet the legal requirements of the agreement which is lawful under the applicable positive law and that the agreement is declared void by law and is considered to be a non-binding agreement.